Sintesis Biosurfaktan Dari Rubber Seed Oil Dan Trietanolamin : Pengaruh Rasio Mol RSOME Dan Trietanolamin Serta Jumlah Katalis KOH - Wibowo, Kusnanto Eko; Irdoni, Irdoni; Nirwana, Nirwana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The surfactant is a substance which has the ability to reduce surface tension, interface tension, and increase the stability of an emulsion. The Surfactant is an intermediate product which is widely applied in the fields of health, pharmacy, industry, and cleaning products in the household. This study makes biosurfactant from rubber seed oil. The purpose of this study is to make biosurfactants from rubber seed oil, to see the effect of reactant mole ratio and amount catalyst of KOH on the biosurfactant characterization produced. The preliminary treatment in this study includes preparation of raw materials, extraction of rubber seed oil by pressing method, the degumming process using phosphoric acid at temperature 90°C for 1 hour, gum separation by centrifuge. The esterification process of oil and methanol with a mole ratio of fatty acid: methanol (1:9), sulfuric acid catalyst (98%) as much as 1 % (b/b) of oil, at temperature 65°C, the process is carried out until ALB < 2%. The transesterification process of methyl ester formation with a mole ratio of oil: methanol (1:9), KOH catalyst as much as 2% (b/b) of oil, at temperature 65°C for 6 hours. In the final stage, the transesterification process of methyl ester becomes esteramine with mixing time 4 hours ,temperature reaction 150°C, stirring speed 200 rpm, mole ratio reactant TEA : RSOME variation 1:2 ; 1:3 ; 1:4, amount catalyst of KOH variation 3%, 5%, and 7%. The best characteristics of biosurfactant were produced at mole ratio reactant 1:2 with amount catalyst KOH as 3% with the density of 0,989 gr/ml, the pH 9,4, ability decrease surface tension 35,43%, ability decrease interface tension 30,43%, the emulsion stability of >95%, the yield 86,96%, and FT-IR test to ascertain amine functional groups in biosurfactant.Keywords: Biosurfactant, rubber seed oil, transesterification, triethanolamine